A paisagem sonora do Parque Ecológico Municipal “Claudino Frâncio” Sorriso–MT : região da Amazônia Legal - Mello, Cilene Leite de (2021)
This study aimed to characterize the soundscape of the Municipal Ecological Park “Claudino Frâncio” in the city of Sorriso – MT, Legal Amazon Region, questioning what is the sound condition of this space, what categories of sounds exist and what is the representativeness of each one. The importance of this investigation is to present the first systematized sound recordings about the Soundscape of this park, and the sound of a place can constitute its identity and meaning. Among the authors surveyed for the conceptual constitution of this work, the following stand out: Schafer (1970), Westerkamp (1974) and Traux (1984). Authors such as Ingold (2011) were used to raise a brief discussion about points raised by Schafer (1970) in relation to listening in an environment, which, in Ingold's view, is not only through the ear, but through all the senses that beings humans have (touch, sight, smell, taste and hearing) and Kelman (2015) proposes to abandon the term soundscape, due to the fact that current studies are very shallow. Another important point highlighted was the author Santos (2002) who comments on the deterritoriality of sound. The methodology used was a case study adopting narrative research, focusing on qualitative research, focusing on the narrations of the park's patrons, with an interview through nine questions about the local soundscape. Twelve recordings were made through sound walks, over two and a half months, alternating in the morning and afternoon periods, in dynamic collections in the drift trajectories. The collected sounds were analyzed and systematized based on the methodology of Schafer (2001) and the Taxonomy of Krause (2011), transforming them into data through a sound map, being represented in tables and organization charts containing the categories of sounds and the creation of a collection of sounds. The most relevant conclusions were that the sounds characterize the culture of a place and the people who frequent it, contributing to demonstrate the state of the place, the sounds that please and dislike. The narratives helped to reveal the transformations that have taken place there over the years, since the founding of the park, stating that man is the subjective constructor of the soundscape of a place.